Pemantauan Kualitas Air: Analisis Logam Berat Timbal (Pb) dan Kadmiun (Cd) Guna Mendukung Kegiatan Perikanan Berkelanjutan di Perairan Jembrana, Bali - Made Dwipa Kusuma Maharani; I Nyoman Dodik Prasetia; Dewi Wulandari; Jasmine Masyitha Amelia; Gressty Sari Br Sitepu (Faculty of Science and Technology University Ibrahimy, 2024)
The purpose of this research was to identify heavy metals in Jembrana waters and analyze water quality to determine water fertility. This study used direct observation and quantitative descriptive. Primary production, biological chemical physical parameters, and heavy metal data were collected in this study. The results showed that Jembrana waters had the highest primary productivity value of 1051.01 mgC/m3/day and the lowest value of 112.61 mgC/m3/day. Water quality in Jembrana is considered quite good. The results of this study showed that the water conditions at the observation site remained stable and within the tolerance limits for marine biota. This is due to the fact that during the sampling period, there was no significant activity from fishermen and local residents. Observations of heavy metals lead and cadmium at the study site showed that some stations exhibited values that exceeded the threshold, but these values were still acceptable for the waters. The heavy metal levels at the stations exceeded the threshold due to sewage effluents from companies and ships in the local harbor.